THE ROLE OF WOMEN IN EFFORTS TO INCREASE WOMEN’S REPRESENTATION IN THE BANJARMASIN CITY COUNCIL FOR THE 2019-2024 PERIOD - Djafar*, Taslim; Aryatama, Muhammad Rizqi; Zaein, Hisya Annasa’i; Unawekla, Stienkha Thysdi (Universitas Padjadjaran, 2024)
This study discusses the Role of Women in Efforts to Increase Women’s Representation in the City Council of Banjarmasin for the Period 2019-2024. The low participation of women in politics in Banjarmasin, especially their representation in the City Council, remains low. The aim of this research is to identify the roles of female council members in promoting women’s representation in the City Council of Banjarmasin, South Kalimantan Province. The research design employed in this study is qualitative research method with data collection techniques through interviews and documentation. The collected data were processed using an inductive approach and analyzed through steps including data reduction, data presentation, and drawing conclusions. This study utilized the Role Theory by Biddle and Thomas as proposed by Sarwono (2015). The research findings from the four dimensions have been successfully implemented. There are supporting factors, such as internal factors like the lack of qualifications and quality among women, minimal support among women themselves, and a public preference leaning more towards men, which pose significant obstacles. External factors such as policies for empowering women, support from civil society organizations, the role of mass media, and societal awareness also play crucial roles. Efforts made include direct actions like empowering women, political education, and quotas or affirmative policies, which are seen as crucial steps to enhance women’s representation in the Banjarmasin City DPRD (Regional People’s Representative Council). Additionally, indirect efforts such as education and increasing gender awareness are considered important, focusing on changing societal views regarding women’s roles in politics and government policy support. These measures aim to improve women’s representation in the Banjarmasin City DPRD by altering societal perceptions of women’s roles in politics and gaining government policy support. All of these are integral to creating an inclusive and equitable environment for political participation for all citizens.